2023
DOI: 10.1021/acs.nanolett.3c00956
|View full text |Cite
|
Sign up to set email alerts
|

Irremovable Mn-Bi Site Mixing in MnBi2Te4

Abstract: MnBi2Te4, an antiferromagnetic topological insulator, was theoretically predicted to have a gapped surface state on its (111) surface. However, a much smaller gapped or even gapless surface state has been observed experimentally, which is thought to be caused by the defects in MnBi2Te4. Here, we have theoretically identified the antisite MnBi and BiMn as dominant defects and revealed their evolution during the phase transition from MnTe/Bi2Te3 to MnBi2Te4. We found that the complete elimination of MnBi and BiM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Intrinsic defect formation energies of bulk MBT in Figure a,b have a reasonable agreement with refs and . However, for the Te-rich chemical potentials, Figure a shows that Mn Bi has the lowest formation energy at the Fermi level, which agrees with ref but disagrees with ref . Importantly, we find that bulk MBT is on the convex hull, in contrast to the positive hull energies of monolayer MBT in Figure .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Intrinsic defect formation energies of bulk MBT in Figure a,b have a reasonable agreement with refs and . However, for the Te-rich chemical potentials, Figure a shows that Mn Bi has the lowest formation energy at the Fermi level, which agrees with ref but disagrees with ref . Importantly, we find that bulk MBT is on the convex hull, in contrast to the positive hull energies of monolayer MBT in Figure .…”
Section: Resultssupporting
confidence: 78%
“…Therefore, complete intrinsic defect studies of bulk MBT and MBYT are performed in Figure to study the Y doping with an increased detail, beyond the screening study. Intrinsic defect formation energies of bulk MBT in Figure a,b have a reasonable agreement with refs and . However, for the Te-rich chemical potentials, Figure a shows that Mn Bi has the lowest formation energy at the Fermi level, which agrees with ref but disagrees with ref .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…It has been found that the Mn-Sb and Mn-Bi site mixings not only affect the topological states of the MST and MBT, but also change their interlayer magnetic couplings. Generally, high concentration of antisite disorder renders the MST topologically trivial [79,80], while the abundance of Mn-Bi antisite defects lead to that MBT and MBT/(BT) n exhibit metallic band behavior [83,85]. However, theoretical calculations and experimental observations reveal that the Mn-Sb and Mn-Bi site mixings are beneficial to realizing interlayer FM coupling in MST, MBT, and MBT/(BT) n .…”
Section: Effective Low-energy Model Analysismentioning
confidence: 99%
“…As the Mn Bi concentration is small, MBT still exhibits an overall A-type AFM ground state (i.e., the interlayer AFM interactions are dominant). In MST, due to similar ionic radii of Sb 3+ and Mn 2+ (smaller than that of Bi 3+ ), a higher Mn–Sb antisite concentration (around 15% Mn Sb and 30% Sb Mn ) is reported when compared to the Mn–Bi antisite concentration (around 5% Mn Bi and 20% Bi Mn ) in MBT. ,,, Therefore, as introduced above, these antisite defects exert significant influences on the overall magnetic structures (AFM or FIM) and transition temperatures of MST. ,, In addition to magnetism, the Mn–Bi/Sb antisite defects would also induce electron/hole doping and alter the Fermi surface, band inversion, and topology of Mn­(Sb/Bi) 2 n +2 Te 3 n +4 . Despite the importance of the defects, their formation mechanism, the methods to tune their concentration and distribution, and how they can control the magnetism remain unclear.…”
Section: Introductionmentioning
confidence: 99%